Creating Excellence in Education Through Digital Storytelling for Tourism Scholars - Srivastava, Surabhi (Integrated Journal for Research in Arts and Humanities, 2025)
Story telling is an effective pedagogical technique that can be used to enhance learning consequences for preferred scientific and technical education. People continue to tell stories using new digital media platforms even now. A digital story can be regarded as a fusion of conventional storytelling and multimedia technology. Furthermore, virtual storytelling enables students to develop their creativity and resolve crucial issues through innovative methods. It is perceived as an engaging approach to developing a promising instructional strategy among tourism students to inculcate a link between knowledge management and knowledge sharing. Higher education in India is not frequently employed to narrate stories. Following induction into the programme, this research examined the teaching experiences of the tourism professors in India. The experience of professors is examined statistically and subjectively through sentiment analysis. The study describes what, how, and why digital storytelling pedagogy is significant for the systematic process of teaching and learning for tourism scholars. This article also examined the expediency of digital storytelling through the TPACK model among professors. The outcome of this research project aims to assist teachers and learners in tapping into the power of digital storytelling and partaking in more engaged tourism teaching and learning. It is therefore recommended for higher education to include a digital story-telling concept for tourism scholars.